Absorption and Elimination of Oat Avenanthramides in Humans after Acute Consumption of Oat Cookies. (21st December 2017) - Zhang, Tianou; Shao, Jing; Gao, Yike; Chen, Chi; Yao, Dan; Chu, Yi Fang; Johnson, Jodee; Kang, Chounghun; Yeo, Dongwook; Ji, Li Li
Abstract : Background . Avenanthramides (AVA) are a group of diphenolic acids found only in oats that have anti-inflammatory and antioxidant effects. Absorption of AVAs in humans after oral consumption of natural oat flour is unknown. Objective . To examine the appearance of AVAs in plasma after oral ingestion of oat cookies and estimate key pharmacokinetic parameters. Methods . Male and female nonobese participants (n = 16 ) consumed three cookies made with oat flour containing high (229.6 mg/kg, H-AVA) or low (32.7 mg/kg, L-AVA) amounts of AVAs, including AVA-A, AVA-B, and AVA-C. Blood samples were collected at 0, 0.5, 1, 2, 3, 5, and 10 h after ingestion. Plasma total (conjugated and free) AVA concentrations were quantified using UPLC-MS, and pharmacokinetic parameters for each AVA were estimated. Results . AVAs reached peak concentrations in plasma between 2 and 3 h for the H-AVA group and between 1 and 2 h for the L-AVA group. Maximal plasma concentrations for AVAs were higher in the H-AVA than in the L-AVA group. AVA-B demonstrated a longer half-life and slower elimination rate than AVA-A and AVA-C. Conclusions . AVAs found naturally in oats are absorbed in the plasma after oral administration in humans. AVA-B has the slowest elimination rate and the longest half-life compared to AVA-A and AVA-C, while AVA-C demonstrated the lowest plasma concentrations. This study is registered with ClinicalTrials.gov identifierNCT02415374 .